ECO-FRIENDLY RECYCLING POTENTIAL OF MICROWAVE MELTING FOR THE RECOVERY OF USEFUL AND PRECIOUS METALS FROM E-WASTE - DUMITRESCU, Daniela Violeta; SOARE, Vasile; CONSTANTIN, Ionuţ; BURADA, Marian; OLARU, Mihai; CÂRLAN, Beatrice; DRĂGOESCU, Marius; VÂLCAN, Angela (Studia Universitatis Babeș-Bolyai Ambientum, 2018)
The processing of waste electrical and electronic equipment (WEEE) has become an issue of significant importance due to the large volumes being generated and to the content of rare and valuable metals as well as environmentally toxic materials (organic compounds). Presently, WEEE is regarded as an important secondary resource of useful metals. The aim of this study is to evaluate the content of base and precious non-ferrous metals in such wastes collected in Romania and to assess the potential of their recycling through processing in microwave field. Electric and electronic wastes are complex mixtures of materials and components, with chemical compositions which depend on their sources (printed circuit boards - PCBs, mobile phones, television and radio sets, home appliances and industrial equipment). In PCBs the metallic fraction is of approximately 30-50 wt.% (with 45-65 wt.% Cu, 0.5-20% Pb, 15-25% Sn, 5-8% Zn, 0.4-0.8% Ag, 0.08-0.2% Au and 2-5% other metals such as Fe, Ni, Al, Sb, Cr, Mn etc.). The non-metallic fractions, which account for 50-70 wt.%, contain substances such as brominated flame retardant, thermosetting resin, reinforced materials and other toxic and hazardous organic compounds. The combustion of these materials during the pyrometallurgical processes may cause serious environmental problems, due to the generation of toxic gases. The microwave melting of WEEE represents a promising state-of-the-art, ecological and energy efficient alternative for the conventional methods with a remarkable applicative potential. The advantages of this method are: i. reduced melting time with energy savings of 30-40%, compared to traditional processes (a microwave furnace can easily attain temperatures up to 1600°C in less than 30 minutes); ii. low content of organic substances. iii. facile extraction of the enclosed metal fractions; iv. improved process control; v. absence of direct contact with the melting materials and vi. environmental-friendly approach through the possibility of treating the toxic gas emissions in a microwave field at high temperatures (1300 ÷ 14000C).